Targeting gut dysbiosis against inflammation and impaired autophagy in Duchenne muscular dystrophy - Hilal Kalkan; Ester Pagano; Debora Paris; Elisabetta Panza; Mariarosaria Cuozzo; Claudia Moriello; Fabiana Piscitelli; Armita Abolghasemi; Elisabetta Gazzerro; Cristoforo Silvestri; Raffaele Capasso; Andrea Motta; et al. (EMBO Molecular Medicine)
Abstract Nothing is known about the potential implication of gut microbiota in skeletal muscle disorders. Here, we provide evidence that fecal microbiota composition along with circulating levels of short‐chain fatty acids (SCFAs) and related metabolites are altered in the mdx mouse model of Duchenne muscular dystrophy (DMD) compared with healthy controls. Supplementation with sodium butyrate (NaB) in mdx mice rescued muscle strength and autophagy, and prevented inflammation associated with excessive endocannabinoid signaling at CB1 receptors to the same extent as deflazacort (DFZ), the standard palliative care for DMD. In LPS‐stimulated C2C12 myoblasts, NaB reduces inflammation, promotes autophagy, and prevents dysregulation of microRNAs targeting the endocannabinoid CB1 receptor gene, in a manner depending on the activation of GPR109A and PPARγ receptors. In sum, we propose a novel disease‐modifying approach in DMD that may have benefits also in other muscular dystrophies.